Strategi Pengelolaan Organisasi Sekolah Dasar dalam Meningkatkan Efektivitas Teknologi Pembelajaran bagi Siswa SDN 1 Puutamboli - Abubakar; Amel; Baharuddin (Digital Pedagogy in Primary Education Journal, 2026)
This study aims to analyze elementary school organizational management strategies for improving the effectiveness of the use of learning technology at SDN 1 Puutamboli. This study employed a qualitative approach, with data collected through observation, interviews, and documentation. The findings indicate that effective organizational management strategies include careful planning, strengthening teachers’ capacities, providing facilities and infrastructure, and supporting the school principal’s leadership. The implementation of these strategies contributes to increased student engagement and improved quality of technology-based learning.   Keywords: school management, learning technology, effectiveness, elementary school, educational leadership